Radiation therapy for vaginal cancer in complete uterine prolapse with intrauterine adhesion: a case report - Ishibashi, Naoya (BMC Womens Health, 2019)
BACKGROUND: We encountered a woman with vaginal cancer that was associated with complete uterine prolapse and complicated by severe intrauterine adhesions. In this case report, we describe the clinical course and successful treatment of this rare condition. CASE PRESENTATION: A 78-year-old woman (gravida 10, para 2, abortion 8) with a 10-year history of uterine prolapse presented for evaluation of bleeding from an ulceration on the surface of the irreducibly prolapsed uterus. Biopsy of a mass on her vaginal wall led to a diagnosis of keratinizing squamous cell carcinoma. Her history of eight abortion procedures had resulted in severe intrauterine adhesions, preventing tandem insertion and intracavitary brachytherapy. She was also ineligible for surgery under general anesthesia + chemotherapy because of her advanced age and presence of arrhythmia. Therefore, we devised an extensive treatment plan involving high-dose-rate interstitial brachytherapy. This treatment successfully eliminated the squamous cell carcinoma as confirmed by biopsy with no recurrence or severe late complications. CONCLUSIONS: We found that high-dose-rate interstitial brachytherapy may be a very effective therapeutic strategy for this condition with few adverse effects.